Controlling the Mediterranean space through surveillance - Maria Gabrielsen Jumbert (Espace populations sociétés, 2013)
The efforts to strengthen the control over the European Union’s (EU) external borders currently revolve around the reinforcement of the surveillance capabilities of the Member States. The European Border Surveillance System, EUROSUR, is supposed to be operational by October 2013, and will enable the Member States to share surveillance data, with the aim of improving the coordination of their responses. The initiative is driven by political motivations (reducing irregular migration into Europe), security objectives (preventing cross-border crime) and a more humanitarian aim (to reduce the death toll at sea among migrants seeking to cross the Mediterranean), with an overarching belief in surveillance technologies as the ultimate way to solve these issues. By virtually pushing the effective border of the EU further out, this future surveillance system however raises a range of legal and ethical dilemmas. This article analyzes the discourse legitimating the need for a more robust surveillance capability at the external borders of the EU, by looking at what can be qualified as the main “drivers”, but also the main points of contention, or “obstacles”, in the process of establishing such a system. It argues that the fundamental belief in surveillance technologies as the ultimate tool to solve the challenges at play along the external border of the EU is such that it only meets the geographical obstacles and legal and ethical dilemmas with a call for more surveillance and more information sharing.